Secretory Leukocyte Protease Inhibitor : A Secreted Pattern Recognition Receptor for Mycobacteria - Gomez, Sonia A. (2009)
Fil: Gomez, Sonia A. Universidad de Buenos Aires. Departamento de Farmacología; Argentina.